Campaigning culinary documentaries and the responsibilization of food crises. Issue 84 (August 2017) - Bell, David; Hollows, Joanne; Jones, Steven
Highlights: The campaigning culinary documentary (CCD) is an emerging food TV format. CCD narrates a food crisis and posits a solution. Readings of selected British TV programmes elaborate its form. CCD is read in the context of neoliberalism and responsibilization. Consumers, the food industry and government are differently responsibilized. Abstract: This paper explores the campaigning culinary documentary (CCD) as an emerging format within food television. CCDs bring together elements of the lifestyle genre with an explicit focus on a food 'crisis' – such as obesity or animal welfare – and explore how this crisis is to be resolved, usually through the intervention of a food celebrity. Focussing largely on shows made by the UK's Channel 4 network, we explore the ways in which CCDs narrate issues of responsibilization, whether these target consumers/viewers, the food industry, or the state. Through a reading of selected CCDs from Channel 4's roster, we consider how the shows attempt to fuse elements of lifestyle/reality TV with a social or political agenda, but one which deploys the governmental strategy of responsibilization and so could be read as an enactment of neoliberal logic. While there is some truth to this claim, our analysis and discussion seeks to complicate this reading, showing how CCDs open up other narrative and political possibilities while also consolidating the brand image of the cookery TV stars who front them.